PENINGKATAN KOMPETENSI SISWA SEKOLAH MENENGAH KEJURUAN MELALUI PELATIHAN PEMROGRAMAN WEB BERBASIS HTML, CSS, DAN JAVASCRIPT - Darmansah; Handoko, Koko; Adhiatma, Novri; Elisa, Erlin (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2026)
The development of digital technology demands increased student programming competency as part of strengthening digital literacy. However, information technology learning in high schools (SMA/SMK) is usually limited to the use of basic software and web programming. The purpose of this community service activity is to improve the skills of SMK Kolese Tiara Bangsa Batam students by teaching them the basics of web programming using HTML, CSS, and JavaScript. The activity was carried out in four stages: preparation, intensive hands-on training, and project-based learning. Evaluation was carried out through pre-tests and post-tests, and program follow-up. The evaluation results showed that the average score increased by 61.6% from 52.4 in the pre-test to 84.7 in the post-test. In addition, 86% of participants were able to complete a simple website project independently. The level of participant satisfaction with the training was very good. The results indicate that the practice-based training approach is effective in improving students' conceptual understanding and technical skills in website development. As a model for continuously strengthening students' digital competencies, this program can be implemented in other schools.